Managing the Intake of Mineral Supplements that Contain Feed Additives for Beef Calves Grazing Flint Hills Native Grass Pasture is Important - R. L. Allison; Z. M. Duncan; C. E. Schneider; W. R. Hollenbeck; K. J. Suhr; B. J. Dedrickson; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective of this study was to determine the efficacy of mineral supplementation programs that provide a performance-enhancing antibiotic for improving growth of stocker calves grazing native grass pastures in the Flint Hills region of Kansas. Experimental Procedures:A 91-day grazing study was conducted at the Kansas State University Beef Stocker Unit starting in May 2020 utilizing 314 Brahman influenced crossbred steers (739.57 ± 10.54 lb) from Gorman, TX. Steers were randomized and allocated across 18 pastures and randomly assigned to three treatments groups with six replications (paddocks) per group. The treatments assessed consisted of standard free-choice mineral: 1) control, 2) Bambermycin, and 3) Monensin. Cattle were weighed individually on day 0 and day 90. Group pasture pen scale weights were taken and recorded on day 0, 45, and 90. Results:During the initial stages of the trial, the consumption of the Monensin treatment was significantly lower than the other two treatments (P<0.05). However, by week seven the Monensin consumption was improved yet still lower than the other two treatments. There were no significant differences in average daily gain (P= 0.72) from the mineral supplement over the 91-day trial. The Bottom Line:Over the 91-day trial, there were no significant differences in average daily gain between the mineral treatments.
Keywords: mineral; stocker; feed additives